Corrosion and Protection of Materials - Cabrini, Marina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book contains thirty articles on various topics related to the corrosion and protection of metallic materials. This topic is of strong actuality both due to the aging of plants and infrastructures that require checks and maintenance, and to the use of traditional materials in increasingly aggressive environments, added to the need of changing the current anti-corrosion systems with less environmental impact methods. Finally, the new development of innovative materials, such as additive manufacturing or high-entropy alloys, needs the characterization of their corrosion behavior. In this issue, there are works on new alloys obtained for additive manufacturing or high entropy, on the study of corrosion and stress corrosion cracking and hydrogen embrittlement mechanisms, through electrochemical and microscopical techniques, studies on low environmental impact inhibitors and biocides, as well as ceramic and metal protective coatings. Finally, there are works on the study of the residual mechanical resistance of corroded infrastructures and on monitoring and non-destructive control. In this way, the book therefore offers a somewhat varied panorama of research trends in the field.